Glue versus mechanical mesh fixation in laparoscopic inguinal hernia repair: meta-analysis and trial sequential analysis of randomized clinical trials. Issue 1 (11th December 2020) - Habib Bedwani, N A R; Kelada, M; Smart, N; Szydlo, R; Patten, D K; Bhargava, A
Abstract: Background: The optimal choice for mesh fixation in laparoscopic inguinal hernia repair (LIHR) has not been well established. This review compared the effects of glue versus mechanical mesh fixation in LIHR on incidence of chronic postoperative inguinal pain (CPIP) and other secondary outcomes, including acute pain, seroma, haematoma, hernia recurrence and other postoperative complications. Methods: A systematic review of English/non-English studies using MEDLINE, the Cochrane Library, OpenGrey, OpenThesis and Web of Science, and searching bibliographies of included studies was completed. Search terms included laparoscopic, hernia, fibrin glue, Tisseel, Tissucol, cyanoacrylate, Glubran and Liquiband. Only RCTs comparing mechanical with glue-based fixation in adult patients (aged over 18 years) that examined CPIP were included. Two authors independently completed risk-of-bias assessment and data extraction against predefined data fields. All pooled analyses were computed using a random-effects model. Results: Fifteen RCTs met the inclusion criteria; 2777 hernias among 2109 patients were assessed. The incidence of CPIP was reduced with use of glue-based fixation (risk ratio (RR) 0.36, 95 per cent c.i. 0.19 to 0.69; P  = 0.002), with moderate heterogeneity that disappeared with sensitivity analysis (8 d.f.) for patient-blinded studies (RR 0.43, 0.27 to 0.86). Trial sequential analysis provided evidence for a relative risk reduction of at least 25 per cent. The incidence of haeamtoma was reduced by using glue-based fixation (RR 0.29, 0.10 to 0.82; P  = 0.02) with no significant effects on seroma formation or hernia recurrence (RR 1.07, 0.46 to 2.47; P  = 0.88). Conclusion: Glue-based mesh fixation appears to reduce the incidence of CPIP and haematoma after LIHR compared with mechanical fixation, with comparable recurrence rates. Abstract : Optimal mesh fixation in laparoscopic inguinal hernia repair (LIHR) has not yet been established. This meta-analysis and trial sequential analysis evaluates the outcomes of glue versus mechanical mesh fixation in LIHR. Glue-based fixation appears to reduce the incidence of Chronic Postoperative Inguinal Pain and haematoma compared to penetrative fixation with comparable recurrence rates. Glue reduces chronic pain. Glue less complications